Competing‐risks analysis in patients with T1 squamous cell carcinoma of the penis. (12th October 2012) - Thuret, Rodolphe; Sun, Maxine; Abdollah, Firas; Budaus, Lars; Shariat, Shahrokh F.; Iborra, François; Guiter, Jacques; Patard, Jean‐Jacques; Karakiewicz, Pierre I.
Abstract : What's known on the subject? and What does the study add? The European Association of Urology (EAU) guidelines recommend an inguinal lymph node dissection (ILND) in patients with T1G2‐3 squamous cell carcinoma of the penis (SCCP). To date, only four series reported the rates of cancer‐specific mortality (CSM) after primary tumor excision (PTE) without an ILND in patients with T1 clinically node‐negative (cN0) SCCP. We examined CSM rates in cN0 patients with T1G1‐3 SCCP, in whom an ILND was not performed, relying on competing‐risks analyses. OBJECTIVE: To quantify and compare cancer‐specific mortality (CSM) and other‐cause mortality (OCM) in individuals with stage T1G1–3 clinically node‐negative (cN0) squamous cell carcinoma of the penis (SCCP) since there is no consensus regarding the need for an inguinal lymph node dissection (ILND) in patients with T1G2–3 cN0 SCCP. METHODS: Relying on the Surveillance, Epidemiology and End Results database, we identified 655 patients diagnosed with primary SCCP between 1988 and 2006. Cumulative incidence plots were used to graphically depict the effect of CSM relative to OCM. Competing‐risks regression analyses were used to quantify the risk of CSM or OCM after adjusting for age, race, tumour grade and surgery type. RESULTS: The 5‐year CSM rates after a primary tumour excision without ILND were 2.6%, 10.0% and 15.9% in patients with respectively T1G1, T1G2 and T1G3 cN0 SCCP. The 5‐year OCM rates were 29.5%, 27.3% and 29.3% in patients with respectively T1G1, T1G2 and T1G3. Age failed to provide additional stratification. CONCLUSIONS: The CSM rate was highest in T1G3 patients and appears to justify ILND. Conversely, the CSM rate was lowest in T1G1 patients, which justifies active surveillance in this patient subset. A moderate CSM rate at 5 years was recorded for T1G2 patients, which brings into question the benefits of ILND.